2007
DOI: 10.1677/jme-07-0007
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel mammalian post-translational modification, phosphocholine, on placental secretory polypeptides

Abstract: Placental neurokinin B appears to be post-translationally modified by phosphocholine (PC) attached to the aspartyl side chain at residue 4 of the mature peptide. Corticotrophin releasing factor (CRF) was found to be expressed by the rat placenta with the main secreted forms being phosphocholinated proCRF+/− one or two polysaccharide moieties. A combination of high-pressure liquid chromatography (HPLC) and two-site immunometric analysis suggested that PC was also attached to the placental precursors of adrenoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 31 publications
(36 reference statements)
0
42
0
Order By: Relevance
“…Even the human host itself can undergo stage-specific modification of proteins with ChoP, such as during pregnancy. It has been shown that placental polypeptides are modified with ChoP, which has been proposed to help shield the fetus from immune recognition (42). In the following sections, the advantages and disadvantages of microbial ChoP expression in different host environments are highlighted.…”
mentioning
confidence: 99%
“…Even the human host itself can undergo stage-specific modification of proteins with ChoP, such as during pregnancy. It has been shown that placental polypeptides are modified with ChoP, which has been proposed to help shield the fetus from immune recognition (42). In the following sections, the advantages and disadvantages of microbial ChoP expression in different host environments are highlighted.…”
mentioning
confidence: 99%
“…3 A, lanes 1-3, and B, lane 1). Because detection of the 14 Ccholine incorporated into the target molecules requires at least 3-wk exposure of X-ray films to the gels, we established a Western blot-based detection with the PC-specific antibody TEPC 15 (21). This antibody recognizes both PC-Rab1 and PC-AnkX but not AMP-Rab1 (Fig.…”
mentioning
confidence: 99%
“…parasites). In parasites it has been suggested that phosphocholine containing proteins are secreted into host organisms and have an effect on immune cells leading to immunosuppression (Lovell et al, 2007). In particular, phosphocholinated proteins in filarial nematodes have been shown to inhibit normal proliferative responses of both T and B lymphocytes in vitro.…”
Section: Phosphocholinationmentioning
confidence: 99%
“…In the placenta, Lovell et al, (Lovell et al, 2007) showed that a large number of placental polypeptides and proteins carry phosphocholine as a tissue specific post translational modification and suggested the presence of phosphocholine groups on placental secretory proteins and peptides may play a major role in maternal immune tolerance during pregnancy. In these studies, placental neurokinin B and the precursors of corticotropin releasing hormone (CRH), adrenocorticotropin, hemokinin, activin and follistatin were shown to be post-translationally modified by the addition of phosphocholine using a combination of HPLC and two site immunometric analyses.…”
Section: Phosphocholinationmentioning
confidence: 99%